Accommodating Students with Disabilities in Higher Education: Rehabilitation Counseling Perspectives - Anuar, Ayob; Merikan, Aren; Nor Mazlina, Ghazali; Edris, Aden; Fatahyah, Yahya (Human Resource Management Academic Research Society (HRMARS), 2018)
Individuals with disabilities are often under presented in higher education setting in which have led these marginalized groups to problems such as having lack of access to academic services and facilities, unequal opportunities to participate in activities on campus thus, hindering their intellectual and psychological growth. As students with disabilities are anticipated to encounter many challenges throughout their academic endeavor, rehabilitation counselors can play integral roles in facilitating these situations. This paper presents the unique roles of rehabilitation counselors and identifies the required competencies to accommodate the academic needs of university students with disabilities. Rehabilitation counselors work collaboratively with the university faculty, staff, and administrators to ensure students with disabilities acquire equal access to academic services and facilities on campus. The required competency when working with students with disabilities in higher education setting is to have a substantial knowledge in psychosocial and medical aspect of disability, vocational rehabilitation counseling, and rehabilitation technology. To create an inclusive and integrated counseling service for student with disabilities, training in the core knowledge area of rehabilitation counseling must be provided to the existing counselors. The inclusion of rehabilitation counseling in the counseling education curriculum will drive the emergence of the field in higher education.